The Influence of the Role of Health Workers, Family Support, and Motivation of Pregnant Women on Compliance with Antenatal Care Visits at the Marawola Community Health Center - Putri Serenggu; Atik Setiawan W; Prima Dewi K; Reni Yuli Astutik; Sentot Imam Suprapto (Journal of Community Health Provision, 2026)
Compliance with Antenatal Care (ANC) visits is an important indicator in efforts to reduce maternal and infant morbidity and mortality rates. However, the coverage of ANC visits in the working area of ​​Marawola Primary Health Center, Sigi Regency, has not yet achieved the national target. Factors presumed to influence compliance with ANC visits include the role of health workers, family support, and maternal motivation. This study aimed to analyze the influence of the role of health workers, family support, and maternal motivation on compliance with ANC visits at Marawola Primary Health Center, Sigi Regency. This study employed a correlational analytic design with a cross-sectional approach. The study population consisted of all third-trimester pregnant women with gestational ages of 35–40 weeks, totaling 175 individuals. A sample of 122 respondents was selected using simple random sampling. Data were collected using questionnaires and analyzed using the Chi-square test and logistic regression analysis with a significance level of α = 0.05. The majority of respondents perceived the role of health workers as good (86.1%), received good family support (77.0%), had high motivation (78.7%), and complied with ANC visits (64.8%). Logistic regression analysis showed that the role of health workers, family support, and maternal motivation had a significant influence on compliance with ANC visits (p < 0.05). The most dominant variable was the role of health workers, with an Exp(B) value of 6.406. The role of health workers, family support, and maternal motivation significantly influences compliance with ANC visits. Strengthening health education, promoting effective communication, and enhancing family involvement in ANC services are necessary to improve pregnant women's compliance with ANC visits.